Os elementos finitos no estudo de eletromagnetismo utilizando os Software Gmsh/GetDP - Malagoni, Juliana Amâncio (2012)
The aim of this master thesis is to study and develop two-dimensional and three-dimensional mathematical models, taking into account Maxwell's equations, the laws of material behavior and boundary conditions. Moreover, have discretization fields by finite element method using the Galerkin approach for electromagnetic analysis, and particularly problems of electrostatics, magnetostatic and electrokinetic. For the development of such a study two freeware computational tools were chosen to use the Gmsh (A Three-Dimensional Finite Element Mesh Generator With Built in Pre and Post Processing Facilities) mesh generator of 3D finite element added to facilities for pre and post processing and the GetDP (General Environment For The Treatment Of Discrete Problems) for the treatment of discrete problems modeled using diferential equations. It was applied the finite element method electrostatic, magnetostatic and electrokinetic formulation for some cases. The first case simulates the electric scalar potential in a two-dimensional and three-dimensional capacitor with a dielectric, the second case simulates the three-dimensional magnetic vector potential of a toroid and the third case simulates a circuit of resistors.